Modelling social dynamics (of obesity) and thresholds - Franz Wirl; Gustav Feichtinger (Games, 2010)
This paper focuses on the dynamic aspects of individual behavior affected by its social embedding, either at large (society-wide norms or averages) or at a local neighborhood. The emphasis is on how initial conditions can affect the long run outcome and to derive, discuss and apply the conditions for such thresholds. For this purpose, intertemporal social pressure (from peers, from norms, or from fashions) is modelled in two different ways: (i) individual benefit is influenced by the possession of a stock (in the application: weight) and the society wide average, and (ii) individual benefits depend on a norm that follows its own motion, of course driven by agents' behavior. The topical issue of obesity serves as motivation and corresponding models and examples are presented and analyzed.
Keywords: 330; obesity; history dependence; social interactions